2015
DOI: 10.14800/crm.893
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic nanomechanical changes in live diabetic cardiomyocytes

Abstract: Patients with diabetes develop a cardiomyopathy that is independent of both coronary artery disease and hypertension and contributes to mortality and morbidity caused by diabetes. The mechanisms underlying the development of diabetic cardiomyopathy are poorly understood. Several reports showed that an early manifestation of diabetic myocardial dysfunction is an increased diastolic left ventricular (LV) stiffness. This increase is usually attributed to myocardial fibrosis or to myocardial deposition of advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…These results may be helpful for studying cardiac disease with accumulation of ECM, such as diabetes, by studying particular interactions between ECM proteins and their integrins on CMs. 49,50 It has been reported that the conformation or function of integrins may be influenced by cations (such as Ca 2+ or Mg 2+ ). 23 Recent study showed that the increment in concentration of extracellular magnesium (from 0 to 5 mM) would enhance the integrins binding ability in human thyroid follicular carcinoma cell line, characterized by AFM and traditional bulk technique.…”
Section: Discussionmentioning
confidence: 99%
“…These results may be helpful for studying cardiac disease with accumulation of ECM, such as diabetes, by studying particular interactions between ECM proteins and their integrins on CMs. 49,50 It has been reported that the conformation or function of integrins may be influenced by cations (such as Ca 2+ or Mg 2+ ). 23 Recent study showed that the increment in concentration of extracellular magnesium (from 0 to 5 mM) would enhance the integrins binding ability in human thyroid follicular carcinoma cell line, characterized by AFM and traditional bulk technique.…”
Section: Discussionmentioning
confidence: 99%